Medication adherence and glycemic control outcomes among type 2 diabetes mellitus patients - Mita Ardila; Haafizah Dania; Siswandi; Woro Harjaningsih; Dyah Aryani Perwitasari; Imaniar Noor Faridah; Adnan; Chatarina Danik Wijayanti; Lidwina Tika Trisnawati; Andri Christianalusi; Ikhwan Dwi Wahyu Nugroho; Dwi Tiva Widyanti (Pharmaciana, 2026)
Type 2 Diabetes Mellitus (T2DM) remains a major public health concern in Indonesia due to its high prevalence and potential to cause various long-term complications when glycemic control is not adequately maintained. Medication adherence and barriers to treatment are important factors that may influence therapeutic outcomes. This study investigated medication adherence, insulin-related treatment barriers, and their association with glycemic outcomes among patients with T2DM at RSPAU dr. Suhardi Hardjolukito Hospital, Yogyakarta. Employing a cross-sectional approach, this research gathered data between September and October 2024. Criteria for eligibility included adult individuals with T2DM who were treated with oral antidiabetic agents, insulin, or both and provided informed consent. Medication-taking behavior was evaluated by utilizing the Medication Adherence Report Scale (MARS-5) framework, while barriers to insulin therapy were evaluated using a specific questionnaire. Associations between adherence status and glycemic parameters were examined through Fisher's Exact Test. A total of 73 patients participated, most of whom were receiving oral therapy (65.8%), a combination of metformin and glimepiride (19.2%), or metformin and acarbose (11.0%). Among insulin users, the majority had low barriers to insulin use (92.0%). Statistical analysis yielded p-values of 0.038 and 0.000 for the associations between medication adherence and fasting blood glucose as well as HbA1c levels, and for the relationship between adherence status and random blood glucose measurements, a p-values = 0.542 was obtained. The findings demonstrated that therapeutic compliance is significantly correlated with both HbA1c and fasting blood sugar levels among individuals suffering from type 2 diabetes mellitus at RSPAU dr. Suhardi Hardjolukito Hospital, Yogyakarta. These results highlight the contribution of adherence behavior to successful glycemic management. Therefore, healthcare professionals are advised to implement strategies that encourage medication adherence to optimize glycemic control.